MENGAPA KOPERASI TIDAK MENYUSUN LAPORAN KEUANGAN SESUAI STANDAR AKUNTANSI KOPERASI ? - Longginus Gelatan (JURNAL ULET (Utility, Earning and Tax), 2022)
The purpose of this study was to analyze the effect of accounting understanding, level of education and supervision on the preparation of financial statements. The method used is the associative method. The type of data used is quantitative data and comes from primary sources. The analytical tool used in this research is multiple linear regression. The results showed that. understanding of accounting has a significant effect on the preparation of financial statements. The poor understanding of accounting causes most cooperatives in Mimika Regency not to prepare financial reports according to cooperative accounting standards. The level of education has a significant effect on the preparation of financial statements. The level of education and training causes most cooperatives in Mimika Regency not to prepare financial reports according to cooperative accounting standards. Cooperative supervision has a significant effect on the preparation of financial statements. The low supervision of cooperatives from both internal and external causes most cooperatives in Mimika Regency not to prepare financial reports according to cooperative accounting standards.